Varietal Screening of Wheat Genotypes against Spot Blotch Disease (Bipolaris sorokiniana) Under Field Condition at Bhairahawa, Nepal - Pandey, A.; Paudel, R.; Kafle, K.; Sharma, M.; Maharjan, N.; Das, N.; Basnet, R. (Journal of the Institute of Agriculture and Animal Science, 2018)
A field experiment was conducted to evaluate the performance of wheat genotypes against spot blotch disease from November 2016 to April 2017. Experimental field was designed in Alpha Lattice Design with 2 replications and 20 genotypes as treatments. Area Under Disease Progress Curve (AUDPC) value, days to heading, days to maturity, plant height, spike per m2, grain per spike, Thousand Kernel Weight (TKW), grain yield were examined. Negative correlation was observed between yield of different genotypes and AUDPC i.e. -0.17322. Genotype BL 4699 and NL 1247 were found to be resistant with AUDPC value 141.7 and 140.6 and yield 3.335MT/ha and 3.604MT/ha respectively. Similarly, genotype BL 4708, NL 1327 and BL 4707 were found to be tolerant with AUDPC value 567.2, 570.6 and 274.6 and yield 3.761MT/ha, 3.642MT/ha and 3.681Mt/ha respectively. So, resistant and tolerant genotypes BL 4699, NL 1247, BL 4708, NL 1327 and BL 4707 could be suggested to incorporate into the breeding program.